PENILAIAN KAPASITAS ORGANISASI PENGELOLA EKOWISATA BERBASIS MASYARAKAT MELALUI ORGANIZATIONAL CAPACITY ASSESSMENT PADA EKOWISATA MANGROVE KOTA SURABAYA - Sasmito Jati U; Sri Umiyati; Sri Wahyuni (UPT Penerbitan Universitas Jember)
Organizational capacity assessment of managing ecotourism based on community is important to do on the organization in determining the capacity enhancement plan, based on a needs assessment of self. Assessment of the capacity of the organization can monitor the effectiveness of previous actions, evaluate progress in increasing capacity and identify areas within the organization managers who need reinforcement. This research aims to examine and assess the conditions existing organizational capacity managing of ecotourism based on community through organizational capacity assessment on Mangrove Ecotourism Wonorejo Rungkut and Wisata Anyar Mangrove Gunung Anyar in Surabaya. The result of the organizational capacity assessment. Methods in this study is elaborate the assessment capacity of UNDP (2008) and Mwiya Mundia (2009). Indicators of governance which is a combined value at the location of the study there is Incipient level. This is different on the indicators, indicators of management practices and service delivery indicators of External Relations on the level of Emerging. On human resources indicators and indicators of sustainability there is a Mature level.